KONSENTRASI CARBOL FUCHSIN DAN WAKTU PENYIMPANAN SEDIAAN HAPUSAN SPUTUM +2 HASIL PEWARNAAN ZIEHL NEELSEN - Fihiruddin Fihiruddin; Nurul Inayati (Jurnal Kesehatan Prima, 2015)
Abstract: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Laboratory diagnosis of TB disease can be confirmed by microscopic examination using the Ziehl Neelsen Methode by carbol fuchsin dye with concentration is 0.3% which it is the standard prosedure. to reduce the error rate of performed sputum smear examination  must be carried out by laboratories established in a network of TB laboratory services. This study aims to determine the concentration of carbol fuchsin and time effective storage of performed sputum smear that show 2+ Ziehl Neelsen staining, and analyze the differences of each carbol fuchsin concentration and storage time. This study was an experimental study. The result showed the average number of acid-resistent bacteria with carbol fuchsin concentration  0.3% is as much as 23, the concentration  1% carbol fuchsin is as much as 54  and the concentration  2% carbol fuchsin is as much as 2. Based on the average amount of storage time, Acid-resistent bacteria (BTA) that storage under 1 month (0 mounth) was available as many as 34, storage for 1 month as many as 28 and stored for 2 months as many as 23, whereas stored for 3 months as many as 18. Based on the survey results know that the concentration of carbol fuchsin that provide maximum results for Ziehl Neelson staining is concentrations 1% and the storage time of performed  sputum smear  2+ is not more than 1 month. Results of statistical analysis indicating that there is significant different at each concentration carbol fuchsin and storage time with of  p value  <0.05.